2017
DOI: 10.1371/journal.pone.0183514
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac computed tomography-derived epicardial fat volume and attenuation independently distinguish patients with and without myocardial infarction

Abstract: Background and objectiveEpicardial adipose tissue (EAT) volume is associated with coronary plaque burden and adverse events. We aimed to determine, whether CT-derived EAT attenuation in addition to EAT volume distinguishes patients with and without myocardial infarction.Methods and resultsIn 94 patients with confirmed or suspected coronary artery disease (aged 66.9±14.7years, 61%male) undergoing cardiac CT imaging as part of clinical workup, EAT volume was retrospectively quantified from non-contrast cardiac C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
60
1
6

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(73 citation statements)
references
References 26 publications
6
60
1
6
Order By: Relevance
“…EAT volume, and more recently attenuation have been increasingly investigated in the literature for associations with cardiac disease 8,[11][12][13][14][15] . Several studies have demonstrated significant cross-sectional relationships www.nature.com/scientificreports www.nature.com/scientificreports/ between EAT and cardiac disease, however a lack of longitudinal data prevents understanding of what therapies or targets may be a modulating factor for EAT.…”
Section: Discussionmentioning
confidence: 99%
“…EAT volume, and more recently attenuation have been increasingly investigated in the literature for associations with cardiac disease 8,[11][12][13][14][15] . Several studies have demonstrated significant cross-sectional relationships www.nature.com/scientificreports www.nature.com/scientificreports/ between EAT and cardiac disease, however a lack of longitudinal data prevents understanding of what therapies or targets may be a modulating factor for EAT.…”
Section: Discussionmentioning
confidence: 99%
“…15 Our EAT radiodensity exploratory findings where we found no association with CAC were consistent with Alvey et al and Lu et al 13, 35 In a study among men and women with confirmed or suspected coronary artery disease, Mahabadi et al found that EAT radiodensity was only mildly correlated with EAT volume and positively associated with type-I myocardial infarction. 36 In a study among primarily male patients suspected of CVD, Marwan et al found that pericoronary fat radiodensity was positively associated with coronary atherosclerotic plaque in unadjusted analyses. 37 …”
Section: Discussionmentioning
confidence: 99%
“…Similarly, in 609 asymptomatic low-risk to intermediate-risk patients, Abazid et al 45 observed a negative correlation between EAT attenuation and coronary calcification independent of EAT volume. In contrast, in a cross-sectional analysis of patients with acute MI and stable CAD controls, Mahabadi et al 27 observed a positive association between EAT attenuation and type I acute MI, while Hell et al 35 did not report a link between EAT attenuation and myocardial ischaemia on SPECT. These contradicting results may be explained by a small sample size, the variable nature of the study population, as well as methodological limitations, such as selection bias, reverse causality and the presence of confounders that were not taken into account.…”
Section: Introductionmentioning
confidence: 91%
“…Indeed, EAT can be easily visualised by routine transthoracic echocardiography and its thickness in the anterior surface of the right ventricle can be measured in a safe and easy manner 26. However, the amount of EAT is more accurately and reproducibly quantified by cardiac CT or MRI 27. Most studies have relied on non-contrast CT scans for EAT segmentation; however, coronary CT angiography provides an optimal method of assessing not only the coronary anatomy, but also specific features of coronary PVAT.…”
Section: Introductionmentioning
confidence: 99%